1993
DOI: 10.1002/eji.1830230916
|View full text |Cite
|
Sign up to set email alerts
|

Somatic hypermutation in 5′ flanking regions of heavy chain antibody variable regions

Abstract: The aim of this study has been to determine the distribution of somatic mutations in the 5' flanking regions of rearranged immunoglobulin heavy chain variable region genes (VDJ). We sequenced the 5' flanking region in 12 secondary immune response antibodies produced in C57BL/6j mice against the hapten (4-hydroxy-3-nitrophenyl)acetyl (NP) coupled to chicken-gamma-globulin. In these and previously published sequences, almost 97% of the mutations occurred in the transcribed region of the gene, and only a minority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…However, the 5' border of the mutation domain in normal Ig genes is in the vicinity of the promoter [15][16][17][18], some 100-200 nucleotides downstream of the transcription start site [19,20]. This positioning of the 5' border of the mutation domain with respect to the start site remains even in the g G-C O transgene when the g -globin gene provides both the promoter and the bulk of the mutation domain (Fig.…”
Section: The Mutation Domain Remains Downstream Of the Promoter Even mentioning
confidence: 99%
“…However, the 5' border of the mutation domain in normal Ig genes is in the vicinity of the promoter [15][16][17][18], some 100-200 nucleotides downstream of the transcription start site [19,20]. This positioning of the 5' border of the mutation domain with respect to the start site remains even in the g G-C O transgene when the g -globin gene provides both the promoter and the bulk of the mutation domain (Fig.…”
Section: The Mutation Domain Remains Downstream Of the Promoter Even mentioning
confidence: 99%
“…This`ligation protection phenomenon' might relate to the presence of a transient DNA hairpin or, alternatively, a covalently bound peptide, which renders the 3' break site inert to the ligation of an adapter molecule. (Lebecque & Gearhart 1990;Peters & Storb 1996;Rothen£uh et al 1993;Weber et al 1991), DSBs are found in an area of 1.3 kb downstream of the promoter and peak around CDR2 and CDR3 (not shown, see Bross et al 2000). The distribution of DSBs (¢gure 3a) along the targeted V H B1-8 gene is remarkably similar to that of the somatic point mutations (Fukita et al 1998).…”
Section: Resultsmentioning
confidence: 96%
“…This would predict that the 5′ edge of SHM could be upstream of its promoter. However, the SHM data clearly show that hypermutations rarely occur 5′ of the promoter 10,139 . Some modifications to this model may be necessary to accommodate this fact.…”
Section: Superhelical Domain Modelmentioning
confidence: 93%